Boundary Value Methods for Caputo Fractional Differential Equations (Journal of Computational Mathematics, 2021)
This paper deals with the numerical computation and analysis for Caputo fractional differential equations (CFDEs). By combining the $p$-order boundary value methods (BVMs) and the $m$-th Lagrange interpolation, a type of extended BVMs for the CFDEs with $γ$-order ($0